DELAYED JUSTICE AND DUAL STANDARDS: THE ENFORCEMENT OF ARBITRAL AWARDS IN PAKISTAN - Siddiqui, Hassan Rasheed (The journal of contemporary issues in business and government, 2010)
This paper critically assesses the issues and systemic challenges associated with the execution of arbitral rulings in Pakistan, specifically focusing on procedural delays and discrepancies arising from conflicting legal positions. Arbitration is supposed to be a quicker and cheaper alternative to litigation but in Pakistan disputants are often faced with immense delay at the enforcement stage due to the tactical use of legal lacunae and difficulty in the High Courts. These obstacles, not infrequently with no real legal justification, are enlisted as weapons to delay the execution of a judgment. The courts have emphasized the distinct handling of foreign and domestic arbitration verdicts in Pakistan, where domestic arbitration is governed by the Arbitration Act of 1940, while foreign awards are regulated by international treaties, including the New York Convention. This mismatch engenders considerable misunderstanding, resulting in inconsistent enforcement that deters foreign investment. The article identifies themes such as the misuse of legal provisions, conflicting standards of legality, and delayed enforcement via semi-structured interviews with important players in the justice system and business community, including attorneys, judges, and arbitrators, as well as a qualitative case study analysis. The study also delineates the devastating consequences these delays have by examining its effects on commerce, the rule of law and foreign investment; thereby pointing out how this lack of efficiency undermines confidence in Pakistan’s arbitration landscape. It is recommended that a single legislative regime covering domestic and international arbitration, strict judicial non-interference and a time-bound enforcement mechanism be adopted under the law. The reforms have been designed to bring Pakistan’s arbitration law in line with international norms, thereby reducing delays, harmonizing with international practices and restoring investor confidence.